Production - Inventory Policies for Deteriorating Items with Imperfect Production Process when Demand is Quadratic (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2010)
This study is aimed at analysing integrated production - inventory policies fordeteriorating items in supply chain when demand of product is subject to increase withtime. The model assumes partial backlogging, imperfect production process and multipledeliveries. The elapsed time until the production process shifts is assumed to beexponentially distributed. It is observed that the joint decision lowers the total costcompared with an independent decisions made by the manufacturer and the retailer with thehelp of numerical data. The sensitivity analysis is carried out to study the variation in thedecision variables and the total integrated cost.
Keywords: integrated production-inventory policy, deterioration, imperfect processes, multiple deliveries, quadratic demand.